Use of Rc4 Method In Android-Based Sms Security Application - Oktovantua Butarbutar (Jurnal Info Sains : Informatika dan Sains, 2021)
. In maintaining the confidentiality of SMS, it takes a way to secure information that is important or confidential, namely by encrypting the SMS text, the level of information security of the message can be increased. One way to use for data and or information security is to use cryptographic system, this application uses RC4 algorithm which has the advantage of having a high level of security and speed process. This makes RC4 the best choice for the encryption process required by the information world towards the next century. The purpose ofbya is to prevent the occurrence of information / data taker without being known by the owner.